Association of bone turnover markers with volumetric bone loss, periosteal apposition, and fracture risk in older men and women: the AGES-Reykjavik longitudinal study. Issue 12 (December 2016) - Marques, E.; Gudnason, V.; Lang, T.; Sigurdsson, G.; Sigurdsson, S.; Aspelund, T.; Siggeirsdottir, K.; Launer, L.; Eiriksdottir, G.; Harris, T.
Abstract Summary Association between serum bone formation and resorption markers and cortical and trabecular bone loss and the concurrent periosteal apposition in a population-based cohort of 1069 older adults was assessed. BTM levels moderately reflect the cellular events at the endosteal and periosteal surfaces but are not associated with fracture risk. Introduction We assessed whether circulating bone formation and resorption markers (BTM) were individual predictors for trabecular and cortical bone loss, periosteal expansion, and fracture risk in older adults aged 66 to 93 years from the AGES-Reykjavik study. Methods The sample for the quantitative computed tomography (QCT)-derived cortical and trabecular BMD and periosteal expansion analysis consisted of 1069 participants (474 men and 595 women) who had complete baseline (2002 to 2006) and follow-up (2007 to 2011) hip QCT scans and serum baseline BTM. During the median follow-up of 11.7 years (range 5.4–12.5), 54 (11.4 %) men and 182 (30.6 %) women sustained at least one fracture of any type. Results Increase in BTM levels was associated with faster cortical and trabecular bone loss at the femoral neck and proximal femur in men and women. Higher BTM levels were positively related with periosteal expansion rate at the femoral neck in men. Markers were not associated with fracture risk. Conclusion This data corroborates the notion from few previous studies that both envelopes are metabolically active and that BTM levels may moderately reflect the cellular events at the endosteal and periosteal surfaces. However, our results do not support the routine use of BTM to assess fracture risk in older men and women. In light of these findings, further studies are justified to examine whether systemic markers of bone turnover might prove useful in monitoring skeletal remodeling events and the effects of current osteoporosis drugs at the periosteum.